Biocompatibility and Solubility of Fe3O4-BSA Conjugates with Human Blood - Stamopoulos, D.; Gogola, V.; Manios, E.; Gourni, E.; Benaki, D.; Niarchos, D.; Pissas, M. (CURRENT NANOSCIENCE, 2009)
Iron oxide Ferromagnetic Nanoparticles (FNs) such as magnetite (Fe3O4) and maghemite (gamma-Fe2O3) are currently employed in biomedical applications owing to their relatively high biocompatibility. Recently, we have introduced a novel application of Fe3O4 FNs in the so-called Magnetically Assisted Haemodialysis (MAHD), a promising concept that can be employed for the treatment of End-Stage Renal Disease. The key characteristic of MAHD is the selective removal of toxins that cannot be removed by current low-and high-flux dialysers that are extendedly used during conventional Haemodialysis (HD). In addition, MAHD could enable the more efficient removal of all toxins when compared to conventional HD so that the duration of dialysis session could be decreased. This is an important benefit that could significantly improve the quality of life of patient. The present work focuses on the in vitro evaluation of the biocompatibility of both bare Fe3O4 FNs and Fe3O4-Bovine Serum Albumin Conjugates (Fe3O4-BSA Cs) with blood cells, namely Red Blood Cells (RBCs), White Blood Cells (WBCs) and Platelets (Plts). Their solubility in whole human blood medium is also carefully evaluated. Both issues are fundamental for the MAHD application since the latter is based on the intravenous injection of FN Cs into the bloodstream of the patient. Atomic force microscopy and optical microscopy were employed for the investigation of both surface characteristics and overall morphology of blood cells, respectively. Samples of donated blood, where bare Fe3O4 FNs or Fe3O4-BSA Cs were added, were maturated under mild incubation for durations up to 120 min. We investigated two representative temperatures, T=20 degrees C owing to easy experimental realization, and T=37 degrees C trying to simulate human body conditions. We did not observe noticeable interference of either bare Fe3O4 FNs or Fe3O4-BSA Cs with RBCs, WBCs and Plts. More importantly we did not observe any degradation of the surface of RBCs and WBCs that were maturated under the presence of bare FNs or Cs in concentrations that strongly exceed the ones used for the treatment of iron-deficiency anaemia. Incidents where either bare FNs or Cs were bound onto the surface of RBCs or internalised by WBCs were very rare. Our observations suggest high biocompatibility of both bare Fe3O4 FNs and Fe3O4-BSA Cs with blood cells, while the solubility depends on the BSA content of the Fe3O4-BSA Cs.